The Outer Limits of Gang Injunctions - Atkinson, Scott E. (2006)
Almost a decade ago, the California Supreme Court endorsed the use of public nuisance injunctions as a means to control street gangs. Public nuisance injunctions against gangs ( gang injunctions ), which result from civil suits filed by district or city attorneys, prohibit the nuisance conduct within a prescribed geographical area, focusing on the turf' claimed by the gang. In People ex rel. Gallo v. Acuna, the California Supreme Court upheld an injunction against thirty-eight named members of a San Jose gang in a four square block area where none of the gang members lived. The court described the neighborhood as an occupied territory and its residents as prisoners in their own homes. To resolve the public nuisance posed by the gang, the Acuna injunction contained a controversial provision prohibiting gang members from publicly associating with each other. The California Supreme Court declared the provision constitutional; such provisions are now common in gang injunctions. Gang injunctions today also frequently limit otherwise legal behavior beyond public association, such as being out after dark, possession of various objects, making gang-related hand signals, and wearing gang colors. Many of the substantive constitutional rights issues raised by Acuna have been critiqued by commentators, but numerous gang injunctions have been imposed since Acuna was decided. Two distinct developments in gang injunction usage warrant deeper examination than existing scholarship provides